Data i lloc de la mort de Jordi de Sant Jordi - Villalmanzo, Jesús (Caplletra. Revista Internacional de Filologia, 2015)
On the basis of the documental evidence presented in the Appendix, the author asserts the fact that the poet Jordi de Sant Jordi died in Barcelona –probably in the Royal Palace– between the 12th and the 15th of june 1424.